Functional characterisation and expression analysis of recombinant serum amyloid P isoform 1 (RbSAP1) from rock bream (Oplegnathus fasciatus). Issue 2 (August 2015) - Choi, Kwang-Min; Shim, Sang Hee; An, Cheul Min; Nam, Bo-Hye; Jeong, Ji-Min; Kim, Ju-Won; Park, Chan-il
Abstract Lectins are carbohydrate-binding proteins that play important roles in the recognition and elimination of pathogens via the innate immune system. Pentraxins (PTX) are humoral lectins, which are multifunctional proteins in vertebrates. Pentraxins can be divided into two groups based on their primary structure: short (C-reactive protein and serum amyloid P [SAP]) and long pentraxins (PTX3 and neuronal pentraxins). Previously, SAP was shown to have Ca2+-dependent binding specificity for various ligands and to be a major acute phase protein. In this study, we identified and characterised the gene encoding SAP isoform 1 in rock bream (Oplegnathus fasciatus) (RbSAP1) and analysed its expression in various tissues after a pathogen challenge. An alignment analysis conducted based on the deduced amino acid sequence of RbSAP1 (1918 bp full-length cDNA with a 699 bp open reading frame encoding 232 amino acids) and SAPs and PTXs isolated from other organisms, revealed that the pentraxin domain and cysteine residues of the deduced protein are conserved. RbSAP1, which was ubiquitously expressed in all tissues examined, was predominantly detected in head kidney, trunk kidney, peripheral blood leukocytes, and gills. RbSAP1 expression was dramatically up-regulated in the kidney and liver after infection with Edwardsiella tarda, Streptococcus iniae, or red seabream iridovirus. Purified rRbSAP1 was able to bind Gram-negative bacteria, Gram-positive bacteria, and pathogen-associated molecular patterns. Interestingly, rRbSAP1 aggregated Gram-negative bacteria in the presence of Ca2+. The anti-pathogen activity of rRbSAP1 suggests that SAP functions in innate immunity in the rock bream.